If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(t + 2) = 72 Reorder the terms: 8(2 + t) = 72 (2 * 8 + t * 8) = 72 (16 + 8t) = 72 Solving 16 + 8t = 72 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 8t = 72 + -16 Combine like terms: 16 + -16 = 0 0 + 8t = 72 + -16 8t = 72 + -16 Combine like terms: 72 + -16 = 56 8t = 56 Divide each side by '8'. t = 7 Simplifying t = 7
| 6n^2-30n^2+24=0 | | (-55/6)=x-(x/2) | | 40=.25x | | 3z+2(4z-2)=5(3-2) | | 8x-7=2x+9 | | 3(2+2x)=18 | | 2(n+2)-8=24 | | 1/2(3a-1)=a-5 | | 4m-4/6m-20 | | 1/4(4t-9)=6 | | 5.5-8.1=-2.6 | | 4f^2-13f+9=0 | | -2(n+2)-8=24 | | .7x-2.9=.6 | | 3n+1=50 | | 6(8x+7)=48x-3 | | 34-2v=5v+6 | | y-12+3y=36 | | 8-3x/8=5/6 | | -1+s+1=5 | | 12x+7(x+1)=102 | | 3h^2+13h+12=0 | | x+y=2x-3y+5 | | 8-3x8=5/6 | | x-2h=3b | | 3x-4y-24=0 | | m=5y+6x | | 4x+64=9x-11 | | 5p^2-49p-10=0 | | (y-5)=4y | | x/8=229 | | -2y+16=32 |